The Role of Tourism Public Relations in Business Continuity Management: An Exploratory Study of a Sample of Employees at the Iraqi Tourism Authority - Dr. Suha Aziz Jaaz (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The tourism sector often faces instability caused by political conditions, security challenges, and fluctuating international perceptions, making organizational resilience and continuity strategies essential for sustainable tourism governance. Specific Background In Iraq, the tourism industry has experienced prolonged structural and reputational challenges that require coordinated communication strategies and institutional preparedness, particularly within the Iraqi Tourism Authority responsible for tourism development and public engagement. Knowledge Gap Despite the recognized strategic value of communication management, limited empirical research has examined how tourism public relations practices support business continuity management in public tourism institutions operating in crisis-prone environments. Aims This study investigates the role of tourism public relations mechanisms in supporting business continuity management within the Iraqi Tourism Authority through an exploratory analysis of employees’ perspectives. Results Using an analytical survey approach with structured questionnaires distributed to employees of the Authority, the findings indicate that organized public relations activities contribute to strengthening communication with target audiences, improving the national tourism image, and supporting institutional preparedness in maintaining tourism operations during challenging conditions. Novelty The study offers empirical evidence from a governmental tourism body in Iraq, highlighting the strategic integration of tourism communication practices with continuity management within a post-crisis tourism environment. Implications The findings suggest that tourism institutions should develop integrated public relations strategies and strengthen cooperation with media, local communities, and tourism stakeholders to support sustainable tourism governance and organizational resilience. Highlights:• Structured Communication Practices Strengthen Engagement With Media, Communities, and Tourism Stakeholders.• Survey Evidence From Institutional Staff Indicates Strong Links Between Communication Strategy and Operational Resilience.• Reputation Recovery and Coordinated Messaging Support Stable Tourism Governance in a Crisis-Affected Environment. Keywords: Tourism Public Relations, Business Continuity Management, Iraqi Tourism Sector, Organizational Communication, Crisis Image Recovery.